COMPARISON OF RETAIL CORPORATE IMAGE BETWEEN ALFAMART AND INDOMARET IN MANADO - Tulong, Rima .; Pandowo, Merinda . (Universitas Sam Ratulangi, 2018)
Abstract: Retail corporate images are perceived as the mental pictures of an organization. It is the sum total of these perceived characteristics of the corporation that refer to as the corporate image. Every organisation has its image. Corporate image is formed based on the stakeholders’ perceptions of specific company actions as well as associated industry and nation issues. An organisation’s image to a large extent influences stakeholders’ reactions to specific corporate actions and products. Alfamart and Indomaret are the two largest retail companies in Indonesia, which are spread from Sabang to Merauke. In 2017 the two companies experienced a decrease in revenue due to administrative and sales costs. The aim of this study is to analyze the retail corporate image between Alfamart and Indomaret in Manado based on store layout, service quality on store, product, in-store promotion, and physical environment. This research is a quantitative research and uses independent sample t-test. The sample size of this research is 100 customers of Alfamart and Indomaret who have already visited and shopped in both stores. The results showed that there is no significant difference in retail corporate image based on store layout, service quality on store, in-store promotion and physical environment between Alfamart and Indomaret while for product there is a significant difference. The recommendation for the research it better for indomaret pay attention for their product. Keywords: retail corporate image, alfamart, indomaret